Sexual consent: Exploring the perceptions of heterosexual and non-heterosexual men. Issue 3 (3rd July 2022) - Sternin, Shulamit; McKie, Raymond M.; Winberg, Carter; Travers, Robb N.; Humphreys, Terry P.; Reissing, Elke D.
ABSTRACT: The current understanding of sexual consent negotiation is grounded in research conducted with heterosexual populations, and little is understood about how non-heterosexual men (bisexual, bi-curious, two-spirited, other) navigate these processes. A sample of 251 heterosexual men and 313 non-heterosexual men participated in an online survey where they were asked to respond to an open-ended question that addressed their perceptions of the differences between how heterosexual and non-heterosexual men negotiate sexual consent. Participants were recruited through social media (i.e. Facebook, Twitter), Amazon's Mechanical Turk, and via the distribution of flyers/posters. The sample consisted of men from Canada, the United States, and Western Europe. Basic demographic information was gathered along with self-identified sexual orientation. Four main themes were derived through the thematic analysis of responses: understanding of sexual interactions, understanding of sexual script, unique challenges, and the universality of sexual consent . Findings provide initial insight into some of the perceived differences and barrier both non-heterosexual and heterosexual men face in negotiating sexual consent and highlight some of the entrenched heteronormative beliefs that both heterosexual and non-heterosexual men endorse. Results can serve to inform social interactions, education, and policymaking.